Organisational phenomena which influence communication and effectiveness - A. B. Boshoff (Communicare)
An overview is given of the traditional or classical views of organisations and organisational functioning. Empirical findings about how organisations really function are presented. It is shown that the organisational model created by the traditional views about organisations is largely an idealisation. The communication problems which develop in organisations are examined in the light of the empirical findings about organisational functioning. A few guidelines for the improvement of communication are presented in the light of the material covered in the paper.